Efeitos dos anestésicos Inalatórios sobre a viabilidade embrionária e a gestação em ratos - Podestá Júnior, Romeu Luiz de (2013)
The study aimed to evaluate the effects of exposure to anesthetics: Halothane (GH), Isoflurane (GI), Sevoflurane (GS) during pregnancy in rats, as well as knowing embryo viability and morphological changes of puppies. A total of 65 female Wistar rats (Rattus norvegicus albinos) were used for exposure to halogenated and matings, distributed into five groups: Group 1 reproductive control (N = 5) pregnant rats not exposed to halogenated, Group 2 (N = 5) rats exposed to halogenated during estrus, Group 3 (N = 5) rats exposed to halogenated during embryogenesis (8th to 10th day of pregnancy), Group 4 (N = 5) rats exposed to halogenated in the fetal period (11 to 13 days pregnancy) and Group 5 (N = 5) rats exposed in the final third of pregnancy (14 to 16 days of pregnancy). A mixture of halogenated and 100% oxygen was administered by face of a cone, for a period of 30 minutes while respecting the MAC of each anesthetic. Signals were observed anesthesia (hypnosis, muscle relaxation, immobility and analgesia) and cardiovascular alterations after administration of each halogenated. The females were undergoing cesarean sections at the end of pregnancy. We evaluated the size, weight and length of the umbilical cords compared with the control group. Histology of uteri and ovaries of pregnant rats was evaluated to observe the effects of halogenated about pregnancy. The procedures were performed in accordance with standards established by the Committee on Research Ethics at the University of Alfenas (Opinion No. 03 rd / 2011). The results showed that the offspring of GH, exposed during estrous (G2) showed weight and smaller size with the control group (G1). The length of the umbilical cord was lower in GH compared to other anesthetics. Fetuses of GI and GS exposed in the first third of gestation (G3) had long cord lower compared to the control group. It was observed that the GI fetuses showed lower weight compared to other anesthetics. In assessing gestational GH showed a lower number of fetuses in the other groups. Histological evaluation of uteri and ovaries of female rats exposed to halothane were observed acute inflammatory reactions that may have influenced the viability of follicles. Blades GI (G3) showed no change endometrial / myometrial. The GS (G3) showed vacuolar degeneration in the myometrium and endometrium and changes in the uterine epithelium. It is concluded that halothane might compromise the estrous period, ie preconceptional acting on the oocytes and ovaries. Exposure to halothane reduced fertility, embryo viability, size and number of fetuses in rats, facts that were not observed with exposure to isoflurane or sevoflurane; these committed the first third of pregnancy, acting on stage embryogenesis. Inhalational anesthesia in rats is safe for development of different experimental procedures, respecting the Minimum Alveolar Concentration (MAC) of anesthetic each employee. The induction and recovery was rapid and the period of anesthesia is safe as long as the necessary precautions are taken primarily with the preconceptional period and the first third of pregnancy, to evaluate properly the risk-benefit ratio for maternal-fetal performing with halogenated analgesia for non-obstetric surgery. It is important to study the anesthetic protocols that provide security to the patient and practitioner in occupational hazard.